2023
DOI: 10.1186/s12916-023-03123-y
|View full text |Cite
|
Sign up to set email alerts
|

Early-life exposure to the Great Chinese Famine and gut microbiome disruption across adulthood for type 2 diabetes: three population-based cohort studies

Wanglong Gou,
Huijun Wang,
Xin-yi Tang
et al.

Abstract: Background The early life stage is critical for the gut microbiota establishment and development. We aimed to investigate the lifelong impact of famine exposure during early life on the adult gut microbial ecosystem and examine the association of famine-induced disturbance in gut microbiota with type 2 diabetes. Methods We profiled the gut microbial composition among 11,513 adults (18–97 years) from three independent cohorts and examined the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The diversity of gut bacteria has been widely considered a crucial characteristic linked to health status and multiple diseases. It has been previously reported that the stability of α‐diversity indicates a healthy status of the intestinal microbiome, and both suppressed and increased α‐diversity represents a signature of gut microbial disorders, which is frequently associated with diseases, including Pon1 ‐related diseases 30–32 . Studies have concluded that the diversity of fecal bacteria is reduced or significantly altered when the host experiences pathological conditions 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of gut bacteria has been widely considered a crucial characteristic linked to health status and multiple diseases. It has been previously reported that the stability of α‐diversity indicates a healthy status of the intestinal microbiome, and both suppressed and increased α‐diversity represents a signature of gut microbial disorders, which is frequently associated with diseases, including Pon1 ‐related diseases 30–32 . Studies have concluded that the diversity of fecal bacteria is reduced or significantly altered when the host experiences pathological conditions 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants born before 1942 were categorized as the adult exposed group and served as the reference group for the study. Others were classified into the following groups based on their age at the time of the famine: infancy and toddler exposed group (born between 1956 to 1958), preschooler exposed group (born between 1953 to 1955), school-aged child exposed group (born between 1947 and 1952), and adolescent exposed group (born between 1942 and 1946) [16].…”
Section: Famine Definitionmentioning
confidence: 99%